Խիկար իմաստունն ու իր խրատները նոր հայեացքով - Յովակիմեան, Արմէն; Կասամանեան, Արմէն (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Авторы представили исследование Погосян максимально подробно, отме- тив, что в нём всесторонне сопоставлены научные мнения об учении мудреца Ахикара. The authors presented Poghossian’s study in as much detail as possible, mentioning that it comprehensively juxtaposes the views of scholars on the teachings of the sage Ahikar.
Keywords: Գրախօսութիւն